Fabrication and Microstructural Analysis of CNTs Reinforced Copper Matrix Nanocomposites via MIM Technique - ., Ali Samer Muhsan, Faiz Ahmad, Norani M Mohamed, M Rafi Raza (2013)
Carbon nanotubes (CNTs) reinforced copper (Cu) mat rix nanocomposites prepared via advanced fabrication method is presented. Functiona lization and ultrasonication processes have been applied to enhance the dispersion of purified CNTs and creates sidewalls groups that have the potential to bond CNTs to the metal matrix. The mai n part of this approach was metal injection molding (MIM) technique, which is a combination of powder metallurgy and plastic injection molding technique. Preparation of MIM feedstock req uired a melting and mixing process of binder system (polymers) with the solid loading, which has been carried out using a twin screw rotor machine. This machine provides a viscous media of t he molten binder with high shear forces that allow the additives (carbon nanotubes/copper powder ) to be mixed properly and exfoliate the CNTs clusters with uniformdispersion inside the Cu matri x. Subsequently, to prove our expected results, observation tests of TEM, SEM, FESEM and CNTS were employed and discussed literally.